(untitled) (Fiep Bulletin - online, 2012)
This socialization is part of the continuing education for engineers and teachers of Early Childhood Education Units - UMEI’s City Department of Education Bethlehem Pa, developed in 2010. It is based on theoretical and methodological Barbier (2007), Moss(2002) Junqueira Filho (2006), Edwards (1999), among others. Our intention is to share experiences built with UMEI’s coordinators, sharing learning, experiences elapsed training practices continued to bet on a proposal to resume play in a continuous movement integrated with expressive languages ??and children’s games. Relevant aspects of this work lie in the ongoing training and development of the pedagogic coordinator who works in child rearing practices and that results in more qualitative valuing the child and childish playfulness ultimately greater involvement of engineers and educators in organization and interactive play areas in early childhood education.